2022
DOI: 10.1101/2022.06.30.498258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircRNA-regulated immune response of Asian honey bee workers to microsporidian infection

Abstract: Nosema ceranae is a widespread fungal parasite for honey bees, causing bee nosemosis. Based on deep sequencing and bioinformatics, identification of circular RNAs (circRNAs) in Apis cerana cerana workers midguts and circRNA-regulated immune response of host to N. ceranae invasion were conducted in this current work, followed by molecular verification of back-splicing sites and expression trends of circRNAs. Here, 10185 and 7405 circRNAs were identified in the midguts of workers at 7 d (AcT1) and 10 d (AcT2) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…A. c. cerana is a subspecies of the eastern honey bee ( Apis cerana ) that is widely reared in China and other Asian countries. In another work, we discovered that the source genes of DEcircRNAs in A. c. cerana workers’ midguts at 7 dpi with V. ceranae were annotated to two immune pathways (for endocytosis and ubiquitin-mediated proteolysis); however, no source genes were enriched in other cellular immune pathways and humoral immune pathways [ 74 ]. Together, these results suggested that various host cellular immune pathways were regulated by corresponding DEcircRNAs through modulation of the transcription of source genes during V. ceranae infestation.…”
Section: Discussionmentioning
confidence: 99%
“…A. c. cerana is a subspecies of the eastern honey bee ( Apis cerana ) that is widely reared in China and other Asian countries. In another work, we discovered that the source genes of DEcircRNAs in A. c. cerana workers’ midguts at 7 dpi with V. ceranae were annotated to two immune pathways (for endocytosis and ubiquitin-mediated proteolysis); however, no source genes were enriched in other cellular immune pathways and humoral immune pathways [ 74 ]. Together, these results suggested that various host cellular immune pathways were regulated by corresponding DEcircRNAs through modulation of the transcription of source genes during V. ceranae infestation.…”
Section: Discussionmentioning
confidence: 99%